(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
This study explores effective teaching strategies for English language instruction. It examines modern pedagogical methods, including communicative language teaching (CLT), task-based learning (TBL), and technology-enhanced learning. Data from various studies suggest that integrating interactive and student-centered methods significantly improves learning outcomes. This article discusses these findings and their implications for educators.